2004
DOI: 10.2166/wst.2004.0028
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of phenol in wastewater at ambient temperature

Abstract: Treating a synthetic wastewater containing phenol as the sole substrate at 26 degrees C, an upflow anaerobic sludge blanket reactor was able to remove over 98% of phenol up to 1,260 mg/l in wastewater with 12 h of hydraulic retention time, corresponding to 6.0 g-COD/(l x day). Results showed that benzoate was the key intermediate of phenol degradation. Conversion of benzoate to methane was suppressed by the presence of phenol. Based on DNA cloning analysis, the sludge was composed of five groups of microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 19 publications
3
28
1
4
Order By: Relevance
“…At a recirculation ratio of 1.0, COD removal also increased to 95% from 92% without recirculation at the same HRT (0.5 d). Similar results were reported by Fang et al (2004) during the treatment of phenolic wastewater employing effluent recirculation at a HRT of 0.5 d and effluent to feed recycle ratio of 1.0. The average effluent volatile fatty acids decreased from 25 mg/L to 15 mg/L.…”
Section: Methodssupporting
confidence: 88%
“…At a recirculation ratio of 1.0, COD removal also increased to 95% from 92% without recirculation at the same HRT (0.5 d). Similar results were reported by Fang et al (2004) during the treatment of phenolic wastewater employing effluent recirculation at a HRT of 0.5 d and effluent to feed recycle ratio of 1.0. The average effluent volatile fatty acids decreased from 25 mg/L to 15 mg/L.…”
Section: Methodssupporting
confidence: 88%
“…More recently, a syntrophic phenol-degrading bacterium (Syntrophorhabdus aromaticivorans) was isolated, and a novel family, Syntrophorhabdaceae (formerly known as Deltaproteobacteria group TA), was proposed (30). Although efforts have been made to identify the specific microbial populations important for the degradation of phenol under anaerobic conditions (9,16,49), microorganisms that grow under well-controlled conditions in the laboratory may not fully represent those in full-scale bioreactors receiving actual wastewater.In our previous study, a Syntrophorhabdaceae-like bacterial population was also found abundantly by fluorescence in situ hybridization (FISH) in a full-scale mesophilic granular activated carbon anaerobic fluidized bed (GAC-AFB) reactor treating phenol-containing wastewater (9). Though the dominance of Syntrophorhabdacea-like populations in a real wastewater treatment system may provide a lead to improving the startup strategy, an in-depth understanding of the exact microbial community in a full-scale plant is necessary to facilitate the development of full-scale processes.…”
mentioning
confidence: 99%
“…It has been reported that phenol concentration up to a range of 500-700 mg/L is generally not inhibitory to the UASB process [16]. Since phenol is anaerobically degradable, the phenol concentration in the bulk solution of the reactor might drop to low levels, particularly after several months of sludge adaptation [17,18]. 5 mg/L 38,048 50 [7]; + Monthly average; -Undetermined…”
Section: Treatment In Uasb Reactorsmentioning
confidence: 99%